1999
DOI: 10.3171/spi.1999.90.2.0178
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of cervical compressive myelopathy with a new dorsolateral decompressive procedure

Abstract: Object. A new dorsolateral decompressive procedure involving a unilateral approach has been devised for the treatment of cervical compressive myelopathy. In this operation, the posterior spinal elements of the contralateral side are not disturbed, and thus, postoperative deformity of the cervical spine can be avoided. Following decompressive surgery via the unilateral approach, the cervical spine was kept more stable compared with the results obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…They found that this rate was significantly increased in the postoperative period. In a study conducted by Hidai et al, a significant increase in the anterior-posterior diameter of the spinal canal was detected after the hemilaminectomy (14). Similarly, Hirabayashi et al observed significant increases in the anterior-posterior diameter of the spinal canal in patients that underwent open door laminoplasty (16).…”
Section: █ Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…They found that this rate was significantly increased in the postoperative period. In a study conducted by Hidai et al, a significant increase in the anterior-posterior diameter of the spinal canal was detected after the hemilaminectomy (14). Similarly, Hirabayashi et al observed significant increases in the anterior-posterior diameter of the spinal canal in patients that underwent open door laminoplasty (16).…”
Section: █ Discussionmentioning
confidence: 92%
“…Hidai et al evaluated patients to whom hemilaminectomy decompression was applied and determined the mean spinal canal area as 169 mm² (14). Ohsawa et al reported the mean spinal canal area in patients that underwent laminoplasty as 144 described the use of laminoplasty in cervical myelopathy which despite the introduction of wide variety of treatment methods including open door laminoplasty, has been among the most widely used methods (17,24).…”
Section: █ Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Preservation of these posterior supporting tissues ensures better postoperative results. 7,11,42,45,47,48,52 In particular, the semispinalis muscles at the C-2 and C-7 levels are important dynamic stabilizers and should be preserved to the fullest extent possible. 3,8,11,17,31,41,44,45,48,51 Preservation of the paravertebral muscles by modified laminoplasty techniques reportedly reduces the incidence of adverse effects of cervical laminoplasty.…”
mentioning
confidence: 99%